Perpanjangan Sertifikat IMDG Barge Pegasus 3 melalui SIMKAPEL di KSOP Kelas I Banten - Riski Seventin Manurung; Suratni Ginting; Yefta Vianus Marbun (Port Management and Maritime Administration Journal, 2026)
The process of extending the International Maritime Dangerous Goods (IMDG) certificate for the Pegasus 3 Barge through SIMKAPEL at the Banten Class I KSOP Office at PT. Pasmaritim Samudera Nusantara, Cilegon Branch. The IMDG Code is intended to protect ship crews and also warn them that their vessels are carrying dangerous goods. An expired International Maritime Dangerous Goods (IMDG) certificate is a crucial step in maintaining a ship's seaworthiness, particularly for vessels transporting dangerous goods. Processing the renewal of an International Maritime Dangerous Goods (IMDG) certificate for a ship is done through the Shipping and Maritime Information System (SIMKAPEL) The Director General of Sea Transportation's system facilitates digital ship certificate renewal services. SIMKAPEL simplifies renewals and saves time and effort by requiring in-person visits to the Banten KSOP office. Service users can access application status anytime and anywhere. The method used in this research was field research namely in the form of direct observation and taking pictures based on the activities of processing ship certificate extensions through SIMKAPEL as well as library research, namely through books in the POLTEK AMI Medan library as well as online books, websites and journals related to the research object.